Finance and sustainability towards a new paradigm? : a post-crisis agenda - Sun, William, 1962-; Louche, Celine; Perez, Roland (Bingley, U.K. : Emerald, 2011)
The recent global financial crisis has indicated that the conventional dominant paradigm in finance is unable to cope with the problems of financial systems, markets, and behaviour of financial institutions, and failed to understand the proper role of finance in society and the economic system as a whole. Drawing on the recent movements of corporate social responsibility, socially responsible investing and sustainable development, this volume goes further to examine the ongoing making of financial reality towards social responsibility and sustainability, and aims at a better understanding of finance as a collective construct and endeavour embedded in societal context. Bringing together leading scholarly thinking this collection opens new avenues of comprehending corporate social responsibility, reveals mechanisms and strategies in shaping the reality of responsible finance, searches alternative approaches towards financial sustainability, and explores new thinking of coping with complex financial choice and financial risks. Moving away from the conventional financial paradigm, this volume demonstrates paradigm shifting in the financial world and provides fresh insights on how we may reshape the financial reality to enable societal betterment and prevent any future financial crisis.
Finance and sustainability : exploring the reality we are making / William Sun, Cine Louche, Roland Pez -- Towards a fiduciary capitalism perspective on business ethics / James P. Hawley --'Corporate social responsibility' : a new regulation of capitalism? : an institutionalist interpretative framework of CSR, based on the French experience / Nicolas Postel, Sandrine Rousseau, Richard Sobel -- CSR and'best interests of the corporation' : new purpose for corporations and managers? : a comparative view from North American and European corporate law / Ivan Tchotourian -- Changing the dominant convention : the role of emerging initiatives in mainstreaming ESG / Hager Jemel-Fornetty, Cine Louche, David Bourghelle -- Activism in European pension funds : exerting pressure on intermediaries / Frank Jan de Graaf, Matthew Haigh -- Drivers of socially responsible investment in the French financial market / Frique D{u296A}ean, Marie-Astrid Le Theule, Bruno Oxibar -- The experimental approach to trust in socially responsible investment funds / Marco Heimann, Sastien Pouget, ienne Mullet, Jean-Fran's Bonnefon -- The strategy and fundamentals of sustainable finance serving sustainable development / Pascal Glain -- In what conditions can venture capital and social justice co-exist? : a case study of a French venture capital fund investing ethically in Africa / Pascale Ch{u3874}eau Terrisse -- Cooperative finance and sustainability after the financial crisis / Rania A. Azmi -- Effects of financialization on restructuring and sustainable development policy : the Accor Group case / Jocelyne Barreau, Juliette Arnal -- Dynamic systems, matching complexity, contributions to corporate financial choice / Zhi H. Wang, Stuart Horsburgh -- The new paradigm in risk management / Daniel Satchkov -- Actual risk sharing measurement in Islamic banks / Kaouther Toumi, Jean-Laurent Viviani, Lotfi Belkacem -- Systemic risk in structured finance : lessons from the ongoing financial crisis / Roberto Violi.
Keywords: Finance; Financial crises